2019
DOI: 10.1038/s41467-019-10122-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Seq enables contamination-free high-throughput single-cell RNA-sequencing for circulating tumor cells

Abstract: Molecular analysis of circulating tumor cells (CTCs) at single-cell resolution offers great promise for cancer diagnostics and therapeutics from simple liquid biopsy. Recent development of massively parallel single-cell RNA-sequencing (scRNA-seq) provides a powerful method to resolve the cellular heterogeneity from gene expression and pathway regulation analysis. However, the scarcity of CTCs and the massive contamination of blood cells limit the utility of currently available technologies. Here, we present Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(173 citation statements)
references
References 51 publications
6
166
0
1
Order By: Relevance
“…The same study also reported heterogeneity concerning PIK3CA mutations [75]. CTCs also often appear heterogeneous in their epithelial-mesenchymal transition (EMT) status [20,35]. Furthermore, a recent study performed CTC analysis from different vascular sites and concluded that CTCs might also exhibit heterogeneity as a function of blood draw location [76].…”
Section: Ctc Heterogeneitymentioning
confidence: 97%
See 1 more Smart Citation
“…The same study also reported heterogeneity concerning PIK3CA mutations [75]. CTCs also often appear heterogeneous in their epithelial-mesenchymal transition (EMT) status [20,35]. Furthermore, a recent study performed CTC analysis from different vascular sites and concluded that CTCs might also exhibit heterogeneity as a function of blood draw location [76].…”
Section: Ctc Heterogeneitymentioning
confidence: 97%
“…Combined with next-generation sequencing (NGS) and mass cytometry technologies, it is now possible to characterize the genome, transcriptome, methylome [18], and proteome [19] of individual cells. The recent development of a single-cell RNA-seq platform based on a hydrodynamic barcoding technique (Hydro-Seq) also shows a promising efficiency for wholetranscriptome analysis of CTCs [20]. As reviewed in the following sections, these approaches have already generated interesting observations, including the identification of oligoclonality in CTCs, the definition of specific molecular profiles in comparisons of primary and metastatic tumors, and the discovery of gene expression signatures that characterize metastatic precursors or differences between CTC subpopulations [21].…”
Section: Molecular Analysis Of Ctcsmentioning
confidence: 99%
“…We further evaluated the pipelines with a human and mouse mixed dataset (Drop-HM dataset) created by mixing a human cell line (HEK) and a mouse cell line (3T3), which is commonly used in evaluating the single cell isolation fidelity of high-throughput scRNA-seq platforms [7,53,54,55]. Ideally, the quantification result of a single cell should only contain transcripts from either species, but not both.…”
Section: Demultiplexing and Transcript Quantificationmentioning
confidence: 99%
“…Recently, Cheng et al combined a scalable hydrodynamic chip with scRNA‐seq barcoding method to capture and analyze rare circulate tumor cells (CTCs) with high‐throughput in a single chip. With efficient capture of CTCs and contamination removal capability from blood samples, this strategy successfully identified breast cancer drug targets and tracked individual cells expressing markers of epithelial/ mesenchymal cell state and cancer stem cells . The cancer heterogeneity study is also extended to clinical applications.…”
Section: Applicationsmentioning
confidence: 99%